IDDF2022-ABS-0262 The impact to food additives in maternal health. (2nd September 2022) - Lv, Chunmei; Liu, Yingzhi; Lin, Winnie; Ching, Jessica; Zhang, Lin; Liu, Yingzhi; Lin, Winnie; Ching, Jessica; Zhang, Lin; Chan, Francis KL; Ng, Siew C
Abstract : Background: Emerging evidence showed that consumption of food additives, artificial sweeteners, contribute to gut dysbiosis and increase offspring's harmful gut. Yet, there is limiting epidemiological studies focusing on the impact of food additives on maternal healthy. Dietary habit that related to the daily maternal pre-pregnancy food additives, artificial sweeteners intake would result in a series of adverse maternal outcomes. Methods: We examined the intake of food additives, artificial sweeteners in pregnant women to replicate the study and observe whether food additives, artificial sweeteners intake are indeed associated with adverse maternal outcomes. This was a prospective study of 380 family pairs population Cohort Study in Foshan, China. Intakes of food additives, artificial sweeteners were assessed by a self-reported food frequency, and food addictive questionnaire. This was a prospective study of 380 family pairs population (The mother-infant microbiota transmission and its link to long term health of baby) Cohort Study in Foshan, China. We examined the intake of food additives, artificial sweeteners in pregnant women to replicate the study and observe whether food additives, artificial sweeteners intake are indeed associated with adverse maternal outcomes. Intakes of food additives, artificial sweeteners were assessed by a self-reported food frequency, and food addictive questionnaire. Adverse maternal outcomes were obtained from the medical system. Results: A total of 372 pregnant women were included. There is a significantly higher alcohol intake for the mothers and fathers who are classified in the higher BMI (mother group=0.0154, father group p=0.0011)(IDDF2022-ABS-0262 Figure 1, Baseline characteristic and BMI). Food additive intake showed higher BMI (mother group p=0.0057, father group p=0.0254) (IDDF2022-ABS-0262 Figure 2, Self Report disease and BMI). Higher aspartame intake showed association with gestational diabetes mellitus (GDM) (adjusted OR:1.9031(95% CI:1.0255, 3, 6591) P<0.05) (IDDF2022-ABS-0262-Figure 3, Current food additive and BMI).Higher Aluminosilicate (AlSiO) intake showed association with (adjusted OR: 0.0813 (95% CI: 0.0147, 0.1478) P=0.0175) (IDDF2022-ABS-0262-figure4) ; Higher Titanium dioxide(TiO2) intake showed association with weight gain (adjusted OR: 0.0678 (95% CI: 0.001, 0.1346) P= 0.0479) (IDDF2022-ABS-0262 Figure 4, Food additive intake and risk of adverse maternal outcomes). Conclusions: This study suggests that a high intake of food additives, artificial sweeteners is associated with an increased risk of GDM. Pre-pregnancy AlSiO and TiO2 intake showed association with weight gain. Higher aspartame intake has an association with higher maternal BMI, weight gain and with an increased risk of GDM. Our findings highlighted the need to better understand how food additive intake may affect the pregnant women.